Cover Picture: Binding of a Designed Anti‐Cancer Drug to the Central Cavity of an RNA Three‐Way Junction (Angew. Chem. Int. Ed. 44/2013). Issue 44 (2nd October 2013) - Phongtongpasuk, Siriporn; Paulus, Susann; Schnabl, Joachim; Sigel, Roland K. O.; Spingler, Bernhard; Hannon, Michael J.; Freisinger, Eva
<x xml:space="preserve">Abstract</x> Recognition and stabilization of an RNA three‐way junction by a supramolecular di‐iron(II) cylindrical complex is described by R. K. O. Sigel, B. Spingler, M. J. Hannon, E. Freisinger et al. in their Communication on page 11513 ff. This potential anti‐cancer metal‐based drug fits perfectly into the central RNA core and stabilizes this architecture in the solid state as well as under native gel conditions. (Cover picture: Joachim Schnabl.)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>